Pay-What-You-Want Pricing - A structured review on drivers of prices paid by customers - Agnes Sophie Roggentin; Mirja Kroschke (Marketing Review St.Gallen, 2017)
Pay-What-You-Want (PWYW) pricing gives customers full control over a transaction price. It is a reasonable strategy to attract new customers, to offset low turnover periods, or for long-term application. The success and applicability of PWYW depends on various company-, customer-, and context-related factors, which will be discussed in this article.
Keywords: 650